MANFAAT DATA PELAYANAN TRANSPORTASI BERBASIS SISTEM INFORMASI TERHADAP PENINGKATAN PARIWISATA SULAWESI TENGAH - Abulebu, Henny Indriyani; Bahar, Taslim; Ramlan, Ratnasari (Universitas Tadulako, 2025)
The development of tourism areas requires good connectivity, including the availability of an integrated and easily accessible transportation system. This study aims to map the condition of transportation mode services in supporting tourism in Central Sulawesi Province and to analyze the integration of transport modes to major tourist destinations in Palu City, Poso Regency, and Tojo Una-Una Regency. Using a descriptive quantitative approach based on secondary data, the study analyzes the accessibility of transportation modes, travel time, and the availability of transport services from city centers to tourist destinations. The results show that the level of transportation accessibility varies across regions, and modal integration improves connectivity between tourism areas, which can contribute to an increase in tourist visits to Central Sulawesi.